The Prevention of Bribery in Government Agencies: The Role of Big Data and Whistle-blowing Systems - Briyan Efflin Syahputra; Anggit Esti Irawati (Jurnal Ilmiah Akuntansi, 2022)
Bribery has become the kind of corruption with the highest annual incidence rate. Therefore, the hunt for solutions to these problems must continue. Consequently, this research must be conducted. The objective is to examine how big data and the whistle-blowing system affect the prevention of bribery. This investigation was conducted utilizing a quantitative methodology. 191 auditors from the Financial and Development Supervisory Agency (BPKP), the Supreme Audit Agency (BPK), and the Indonesian Government Inspectorate were surveyed via distributing questionnaires. This research employs structural equation modeling (SEM) with the assistance of the smartPLS application for statistical testing. Both big data and the whistle-blowing system have proven to have a positive impact on bribery prevention, according to the findings of this study.